2020
DOI: 10.7770/safer-v0n0-art1555
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of heavy metals in agricultural soils from Katsina state Nigeria

Abstract: This work contributes to the monitoring of Agricultural soil pollution in Katsina State, North western Nigeria by assessing the degree of heavy metal pollution in Agricultural soil samples. The study was conducted in the year 2017 within some catchment areas located within the 3 senatorial zones that constitute to make up the state (Katsina senatorial zone: Birchi, Dutsinma and Katsina; Daura senatorial zone: Daura, Ingawa and Zango; Funtua senatorial zone: Dabai, Funtua, Kafur, Malunfashi and Matazu).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
8
1
Order By: Relevance
“…The mean levels of heavy metals (mg/kg) in contaminated soils were significantly (p<0.05) higher compared with those from the uncontaminated site (Control) as shown in Table 1. The result for the mean heavy metal concentration was higher than the results reported in a study that evaluated heavy metal concentrations of soil samples in Katsina state Nigeria [26]. Key: MAC=Maximum Allowable Concentration; Source: a=Bowen [25], b= Awokunmi et al [27], c=ATSDR [28] The results in Table 1 showed that the soils in Challawa Industrial Estate are contaminated with heavy metals (Cd, Cr, Cu, Fe, Mn, Ni, Pb and Zn) and their pH was slightly acidic.…”
Section: Resultscontrasting
confidence: 84%
“…The mean levels of heavy metals (mg/kg) in contaminated soils were significantly (p<0.05) higher compared with those from the uncontaminated site (Control) as shown in Table 1. The result for the mean heavy metal concentration was higher than the results reported in a study that evaluated heavy metal concentrations of soil samples in Katsina state Nigeria [26]. Key: MAC=Maximum Allowable Concentration; Source: a=Bowen [25], b= Awokunmi et al [27], c=ATSDR [28] The results in Table 1 showed that the soils in Challawa Industrial Estate are contaminated with heavy metals (Cd, Cr, Cu, Fe, Mn, Ni, Pb and Zn) and their pH was slightly acidic.…”
Section: Resultscontrasting
confidence: 84%
“…State are increasingly being contaminated with heavy metals via numerous pollution channels such as horticultural practices, mining and automotive exhaust [6][7][8].…”
Section: Farmlands Used For Agricultural Activities In Katsinamentioning
confidence: 99%
“…are continuously being loaded with heavy metals from several pollution sources, such as agricultural practices, mining and vehicular exhaust [6,7,8]. The northwestern part of Nigeria where Katsina State is located has of recent, recorded a surge in cattle rustling, kidnappings and rural banditry, with most of the bandits been drawn to the region by illicit and artisanal mining [9].…”
Section: Original Research Articlementioning
confidence: 99%
“…∑1 n =ILCR 1 + ILCR 2 +⋯+ILCR n… ……..eqn. (6) With the subscripts 1, 2 …, n representing each carcinogenic heavy metal.…”
Section: Ilcr = CDI X Csf …………………Eqn (4)mentioning
confidence: 99%